A pilot study on the use of DNA metabarcoding for diet analysis in a montane amphibian population from North Africa. Issue 1 (2nd January 2021) - Pereira, Ana; Samlali, Mohamed Amine; S'Khifa, Abderrahim; Slimani, Tahar; Harris, D James
ABSTRACT: Although dietary studies are essential to design effective conservation strategies for amphibians, non-invasive studies using microscopy assessment of faecal material are known to have limitations. We assessed the use of DNA metabarcoding to determine diet in the Moroccan painted frog Discoglossus scovazzi . Nineteen families of insects were identified, and resolution of prey taxonomy to the family level identified differences between adult males and females not seen at the order level. Several prey items could be identified to the species level, providing identifications that add towards the determination of the insect diversity of the habitat. However, the 16S primers used only amplified insect prey, so a notable part of the diet could not be surveyed. Multiple markers will be needed to obtain information across the whole prey spectrum of these generalist amphibians.